Capital Flows and Money Supply: The Degree of Sterilisation in Pakistan (The Pakistan Development Review, 2003)
Under the current managed float exchange rate system; the central bank may respond to an exchange market disequilibria by changing either the international reserves or the exchange rates. Under such a regime, a major policy difficulty is the interaction between exchange rate policies and monetary policies. The monetary authorities intervene in the exchange market in response to undesired fluctuations in exchange rates,1 could adversely affect monetary control and move the economy away from internal target such as price stability. Under such a policy dilemma, fully sterilised intervention2 involves a pure swap of foreign and domestic assets, which have not effect on the money supply, received greater attention by the policy-makers in early 1980s, particularly, through the experience of West Germany [Obstfeld (1983)]. Ideally, it provides an independent policy tool to deal with the exchange rate without affecting the internal policy targets.